(untitled) (Oxford, 2001)
Like the popular first edition, this new edition of Proteolytic Enzymes emphasizes practical aspects of the handling, characterization, inhibition, and use of proteolytic enzymes giving general advice and specific examples. The text and protocols have been thoroughly updated to take account of the advances made in the last 10 years in both the increased understanding of the role of peptidases in many critical cellular processes e.g. apoptosis and new technological developments e.g. in recombinant protein expression, protein sequencing, and structural studies. The topics covered are: nomenclature and classification; purification; assay methods; determination of mechanism; inhibition and prevention of unwanted proteolytic activity; characterizing natural inhibitors; proteolytic enzymes in peptide mapping and primary structure elucidation by mass spectrometry and Edman sequencing; limited proteolysis as a structural probe; synthetic function. This book will be as invaluable as the first edition in providing ideas and protocols for scientists either studying proteases or using proteases as a research tool.
Keywords: Proteolytic enzymes,Enzyme phân hủy protein